Working in Public Accounting: An Analysis of the Differences of Auditors' Work-life Balance and Working Hours between the United States and Switzerland - Kapernick, Christopher N. (2017)
As the existing research clearly suggests, the amount of hours auditors have to work is seen as one of the main issues threatening the long-term sustainability of the audit profession. These long hours have a direct impact on the work-life balance of audit professionals, which is a major concern for the future outlook of the profession considering the focus of the future workforce is to maintain a satisfying work-life balance when deciding on a job. This paper addresses the question if there are any differences between the amount of hours auditors have to work in Switzerland and the United States, and if they also differ in how satisfied they are with their current work-life balance. The majority of existing research has focused on auditors in the United States. This research aimed to identify the differences to Switzerland, which could also result in possible solutions to improve the overall work conditions of the auditors. The main method used to generate the results was of quantitative nature in the form of a questionnaire consisting of 15 questions that were targeted to expose the differences between the two countries. The results clearly showed a difference between the United States and Switzerland and indicated that auditors in the United States have to work much longer hours during the busy season. Perhaps, as a result of the differences in working hours, differences in the level of satisfaction concerning the work-life balance of auditors were also exposed. Swiss auditors seem to be more satisfied with their work-life balance and generally seem to have a better work experience than their American colleagues. The results of this research show a danger to the audit profession, especially in the United States, but also provide a possible solution if the Big 4 firms would take Switzerland as an example. Further research would be required to find out what exactly causes the differences that were uncovered through this research. However, the better conditions for auditors in Switzerland that were revealed through my research indicate that extremely long working hours and low job satisfaction are not necessarily a global issue, but maybe more specific to the United States.